IMPACT OF THE PHYSICAL EDUCATION TEACHER ON STUDENTS' POSITIVE AFFECT (Fiep Bulletin - online, 2025)
Introduction: Physical education in Mexico faces challenges in the motivation and engagement of high school students. This study aims to analyze the interrelationships between the quality of homework presentation by the physical education teacher, the satisfaction of the need for novelty and the positive affect of high school students in Aguascalientes, Mexico. Methodology: The research, correlational and cross-sectional in nature, involved 398 students aged 11 to 14 years. Descriptive analyses, reliability and correlations calculations using SPSS v27, as well as confirmatory factor analysis and structural equations with AMOS v24 were used. Results: The results reveal that when testing the models, the results indicated that task presentation was positively and significantly associated with novelty satisfaction as well as novelty satisfaction with positive affect, and when a direct relationship was made between task presentation and positive affect, this relationship was not significant, indicating that there was a total mediation by novelty satisfaction. Conclusion: It is concluded that the quality of task presentation by the physical education teacher significantly influences students' need for novelty satisfaction and is associated with their positive affect, which could have important implications for students' motivation and engagement in physical education classes.
Keywords: Novelty; basic psychological needs; self-determination theory; physical activity; positive affect